Handbook of differential equations. Evolutionary equations. Volume 4 - Dafermos, C. M. (Constantine M.); Feireisl, Eduard; ScienceDirect eBooks (Amsterdam : Elsevier, 2008)
The material collected in this volume discusses the present as well as expected future directions of development of the field with particular emphasis on applications. The seven survey articles present different topics in Evolutionary PDE's, written by leading experts. - Review of new results in the area - Continuation of previous volumes in the handbook series covering Evolutionary PDEs - Written by leading experts.
Incompressible Euler Equations (D. Chae) -- Large time behaviour of solutions to PDE's (A. Miranville, S. Zelik) -- Cahn-Hiliard Equation (A. Novick-Cohen) Mathematical theory of viscoelastic fluids (M. Renardy) -- Theory of functional parabolic equations (L. Simon)Hydrodynamical limists (A. Vasseur) -- Theory of Korteweg-de Vries equation (A. Wazwaz).
Includes bibliographical references and index.
Print version record.
Elsevier
Keywords: Differential equations -- Handbooks, manuals, etc; Evolution equations; Differential equations; Evolution equations; Electronic books